The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1063/1.4917208
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conduction mechanism in bulk ceramic insulators at high voltages until dielectric breakdown

Abstract: Electrical characteristics and conduction mechanisms of metal-insulator-metal capacitors with nanolaminated Al 2 O 3 -Hf O 2 dielectrics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…The data is fitted with straight line in these two regions and the obtained slope values are 1.10 ± 0.03 and 2.10 ± 0.03 for the low and high applied field regions respectively. These values indicate that Ohmic conduction and space charge limited conduction mechanisms are dominating conduction mechanism at low and high applied fields respectively similar to that of most of the polycrystalline ceramics[7,11,12].…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The data is fitted with straight line in these two regions and the obtained slope values are 1.10 ± 0.03 and 2.10 ± 0.03 for the low and high applied field regions respectively. These values indicate that Ohmic conduction and space charge limited conduction mechanisms are dominating conduction mechanism at low and high applied fields respectively similar to that of most of the polycrystalline ceramics[7,11,12].…”
mentioning
confidence: 82%
“…One can see that J-E curves exhibit good symmetry about positive and negative field values. Neusel et al, recently reported the Importance of the study of dielectric breakdown and various mechanisms contributing to it in bulk insulators especially metal oxide ceramics[7]. Further to get insight into the mechanisms that are contributing to the observed J-E data, the data is plotted in terms of ln(E) versus ln(J) as shown in the inset of figure-4.…”
mentioning
confidence: 98%
“…For the perfect alumina crystal, the electrical carriers are mainly the electrons in the conduction band and the holes in the valence band that are generated by the thermal excitation. When the electric field is high, space charge limited conduction is the dominant conduction mechanism [28,29]. In the thermal DB theory and the avalanche DB theory, the large current induced by the strong electric field can lead to more excited electrical carriers and subsequently the DB.…”
Section: Analyses On the Underlying Mechanisms Behind The Effects Omentioning
confidence: 99%
“…A proportionality of dielectric strength to the −0.5 power of relative permittivity is shown by different groups of researchers [8,9]. Trapping of charges [10,11] and space charge limited conductivity [12][13][14] are recently discussed to be decisive for breakdown channel formation in ceramics.…”
Section: Introductionmentioning
confidence: 99%